Determining the temporal, dose, and composition effects of nutritional substrates in an in vitro model of intrahepatocellular triglyceride accumulation. Issue 20 (27th October 2022) - Nagarajan, Shilpa R.; Cross, Eloise; Johnson, Elspeth; Sanna, Fabio; Daniels, Lorna J.; Ray, David W.; Hodson, Leanne
Abstract: Pathological accumulation of intrahepatic triglyceride underpins the early stages of nonalcoholic fatty liver disease (NAFLD) and can progress to fibrosis, cirrhosis, and cancer of the liver. Studies in humans suggest that consumption of a diet enriched in saturated compared to unsaturated fatty acids (FAs), is more detrimental to liver fat accumulation and metabolism. However, the reasons for the divergence remain unclear and physiologically‐relevant cellular models are required. Therefore, the aims of this study were to investigate the effect of modifying media composition, concentration, and treatment frequency of sugars, FAs and insulin on intrahepatocellular triglyceride content and intracellular glucose, FA and circadian function. Huh7 cells were treated with 2% human serum and a combination of sugars and FAs (low fat low sugar [LFLS], high fat low sugar [HFLS], or high fat high sugar [HFHS]) enriched in either unsaturated (OPLA) or saturated (POLA) FAs for 2, 4, or 7 days with a daily or alternating treatment regime. Stable isotope tracers were utilized to investigate basal and/or insulin‐responsive changes in hepatocyte metabolism in response to different treatment regimes. Cell viability, media biochemistry, intracellular metabolism, and circadian biology were quantified. The FA composition of the media (OPLA vs. POLA) did not influence cell viability or intracellular triglyceride content in hepatocytes. In contrast, POLA‐treated cells had lower FA oxidation and media acetate, and with higher FA concentrations, displayed lower intracellular glycogen content and diminished insulin stimulation of glycogenesis, compared to OPLA‐treated cells. The addition of HFHS also had profound effects on circadian oscillation and gene expression. Cells treated daily with HFHS for at least 4 days resulted in a cellular model displaying characteristics of early stage NAFLD seen in humans. Repeated treatment for longer durations (≥7 days) may provide opportunities to investigate lipid and glucose metabolism in more severe stages of NAFLD.